A pseudo thermo-mechanical model linking process parameters to microstructural evolution in multilayer additive friction stir deposition of magnesium alloy. (December 2022) - Sharma, Shashank; Mani Krishna, K.V.; Radhakrishnan, M.; Pantawane, Mangesh V.; Patil, Shreyash M.; Joshi, Sameehan S.; Banerjee, Rajarshi; Dahotre, Narendra B.
Graphical abstract: Highlights: A multi-layer pseudo thermo-mechanical model considering frictional heating and plastic deformation have been developed for additive friction stir deposition. The pseudo thermo-mechanical model provides reasonable accuracy and computational efficiency (run time < 20 min for 5 layers). Simulations reveal the effect of process parameters (rotational speed, and traverse speed) on temperature and strain rates during AFSD. EBSD and TEM analysis suggested occurrence of dynamic recrystallization followed by grain coarsening during multi-layer depositions. Phenomenological relationship between Zener-Holloman parameter and grain size elucidates unique thermo-mechanical imprint on microstructure evolution during AFSD. Abstract: Additive friction stir deposition has been proposed as a disruptive manufacturing process; involving complex thermo-mechanical mechanisms during multilayer material deposition. The current efforts have attempted to develop a FEM based pseudo-mechanical thermal model accounting for heat generation due to friction and plastic dissipation during multilayer additive friction stir deposition. The primary motivation for development of the model was to seek an understanding of thermo-mechanical mechanisms and their impact on microstructural evolution during additive friction stir deposition. The predicted temperature–time profiles agreed well with the experimentally derived ones. The computational predictions indicate rise of the peak temperatures up to 0.8 times the melting temperature of Mg-alloy. In addition, the Zener-Holloman parameter, Ze evaluated using the computational model was correlated with the microstructural evolution during the deposition process. The unique thermo-mechanical processing conditions during additive friction stir deposition led to dynamic recrystallization followed by grain coarsening. A significant extent of texture strengthening was observed in the AFSD processed samples. The already established phenomenological relationship between Ze and grain size was used to predict the grain size in the present work. The computational predictions indicate that the recrystallized grain size ranged from 4 to 6 µm, and the post deformation grain coarsening varied in the range of 4–24 µm, thereby providing reasonable agreement with the experimental observations.